A computerized scoring system to improve assessment of heparin‐induced thrombocytopenia risk. (22nd January 2019) - Gallo, T.; Curry, S. C.; Padilla‐Jones, A.; Heise, C. W.; Ramos, K. S.; Woosley, R. L.; Raschke, R. A.
Abstract : Essentials Current risk scores for heparin‐induced thrombocytopenia (HIT) are not computer‐friendly. We compared a new computerized risk score with the 4Ts score in a large healthcare system. The computerized risk score agrees with the 4Ts score 85% of the time. The new score could potentially improve HIT diagnosis via incorporation into decision support. Summary: Background: (HIT) is an immune‐mediated adverse drug event associated with life‐threatening thrombotic complications. The 4Ts score is widely used to estimate the risk for HIT and guide diagnostic testing, but it is not easily amenable to computerized clinical decision support (CDS) implementation. Objectives: Our main objective was to develop an HIT computerized risk (HIT‐CR) scoring system that provides platelet count surveillance for timing and degree of thrombocytopenia to identify those for whom diagnostic testing should be considered. Our secondary objective was to evaluate clinical management and subsequent outcomes in those identified as being at risk for HIT. Methods: We retrospectively analyzed data from a stratified sample of 150 inpatients treated with heparin to compare the performance of the HIT‐CR scoring system with that of a clinically calculated 4Ts score. We took a 4Ts score of ≥ 4 as the gold standard to determine whether HIT diagnostic testing should be performed. Results: The best cutoff point of the HIT‐CR score was a score of 3, which yielded 85% raw agreement with the 4Ts score and a kappa of 0.69 (95% confidence interval 0.57–0.81). Ninety per cent of patients with 4Ts score of ≥ 4 failed to undergo conventionally recommended diagnostic testing; 38% of these experienced persistent, unexplained thrombocytopenia, and 4% suffered life‐threatening thrombotic complications suggestive of undiagnosed HIT. Conclusion: The HIT‐CR scoring system is practical for computerized CDS, agrees well with the 4Ts score, and should be prospectively evaluated for its ability to identify patients who should be tested for HIT.